ANALYSIS OF THE ACCIDENTS OF THE CAR MANUFACTURING INDUSTRIES - J.Adl ; Z. Mohammad zade (Tehran University of Medical Sciences, 1993)
Car manufacturing industry accident's rates from three major companies are analyzed. Totally 1325 accidents with 4 cases of fatality were recorded. Accident rates per 100 full-time workers have gradually increased from 5.3 to 8.7 during 3 years of study. Most of the accidents occurred during the primary hours of the work, Strains and sprains represented the most frequently occurring type of injury, accounting for 37.9% and the greatest number of injuries occurred by flying particles (3 1.6%), resulting in eye injuries. Other aspects of accidents in this industry are discussed and recommendations are given for their prevention.